A look at the last civil-military-ecclesiastical dictatorship from the towns of the Argentinean NOA: the trilogy of novels by Gloria Lisé - Marcela Crespo Buiturón (Estudios de Teoría Literaria, 2025)
Gloria Lisé began writing her trilogy, Viene clareando (2005), Paisaje de final de época (2012) and Cuando yo lo encuentre (2024), exploring the limits of fiction, its suspicious links with the personal and social memory of the most violent chapter of our recent history: the last civil-military-ecclesiastical dictatorship. Illuminating the absent dimension not only of the disappeared bodies, but also of the people of the interior of the provinces of the Argentine NOA, erased or discarded by the Argentine State, the novels breathe life into the other voices of history, severely questioning the totalisations of meaning of the hegemonic discourses, and questioning the responsibilities of both the repressive forces and the complicit societies.